(untitled) - Carlos, C.R.=700 1 Costa, J.R.; Tao, C.B.; Torres, L.M.
(En, Es)
ilus., 15 ref.
Parasitismo aáociado a traca-da-uva, Lobesia botrana (Denis Schiffermuller) na Regiao Demarcada do Douro
Keywords: LOBESIA BOTRANA; PARASITOIDES; VID; ESPAÑA; ELACHERTUS AFFINIS; BRACHYMERIA; CAMPOPLES CAPITATOR; DIBRACHYS CAVUS; VITICULTURA